Investigating root and canal morphology of anterior and premolar teeth using CBCT with a novel coding classification system in Saudi subpopulation - Mohammed Mustafa; Mohmed Isaqali Karobari; Ali Abdullah Alwan Al-Maqtari; Abdulaziz Abdulwahed; Ahmed A. Almokhatieb; Laila S. Almufleh; Qamar Hashem; Abdullah Alsakaker; Mohammad Khursheed Alam; Hany Mohamed Aly Ahmed (Scientific Reports)
Abstract Understanding root canal morphology is essential for successful endodontic treatment. This study aimed to investigate morphological variations in root and canal systems of anterior and premolar teeth across different age groups and genders in a Saudi Arabian subpopulation using a novel classification system. A total of 3573 maxillary and mandibular anterior and premolar teeth in 209 patients were examined using cone-beam computed tomography (CBCT) in a Saudi subpopulation. The number of roots was identified, and root canal configurations were classified according to Ahmed et al. coding system (Int Endod J 50(8):761–770, 2017). Demographic data including gender (male and female) and age (divided into 6 groups—10–20, > 20–30, > 30–40, > 40–50, > 50–60, > 60–70) were recorded. The Chi-square test was used for statistical analysis, and the significance level was set at 0.05 (P = 0.05). Results showed that maxillary and mandibular central incisors, lateral incisors, and canines predominantly exhibited the 1TN1 configuration. Maxillary first premolars had a higher prevalence of double-rooted variants with code 2TN B1 P1. Maxillary second premolars more frequently displayed the 1TN1–2−1 configuration. No significant gender and age differences were observed in maxillary anterior and premolar teeth (p > 0.05). A number of supplemental configurations such as 2TNB1–2P1, 3TN MB1 DB1 P1, and 3TN 1(MB1 DB1) P1 were noted in maxillary premolars. For mandibular anteriors, results showed no significant difference by gender, but for age, mandibular incisors showed more prevalence of complex canal configurations up to 40 years. However, the difference with other age groups (> 40–70 years) was not statistically significant (p < 0.05). For mandibular premolars, the code 1TN1 was observed in more than 90% of the teeth with no significant differences in gender and age groups (p > 0.05). Several supplemental configurations such as 1TN1–2−3, 1TN1–2−3−2, 2TN B1/L1, and 2TN 1B1/L1) were noted in mandibular first premolars. This study identified a wide range of root and canal anatomical variations in anterior and premolar teeth within a Saudi subpopulation. The findings revealed that while age influenced the complexity of root canal systems in mandibular incisors, no significant association between gender and canal complexity was observed. The Ahmed et al. classification system offered a detailed analysis of these complex variations, providing a clear understanding of the root canal morphology in this population.